A Literature Review On Lokanatha Rasa with special reference to Liver and Spleen Disorders - Herapathdeniya, S.K.M.K.; Paranagama, P.A.; Ranasinghe, S. (Institute of Indigenous Medicine, University of Colombo., 2021)
Ayurveda pharmaceutics deal with herbal, mineral and animal materials. Description of mineral materials and their preparation are described in a special branch of Ayurveda pharmaceutics, Rasa shastra. It mainly deals with mercury, minerals, metals, gems and some toxic plant materials. All preparations mentioned ...
Keywords: Lokantha rasa; Rasa shastra; Rasa aushadies; Putapaka; Pottali